Предмет: Алгебра,
автор: samandar0613
Разложите на множители
a(b-c)-c(c-b)
Ответы
Автор ответа:
4
Ответ:
================================
a(b - c) - c(c - b) = a(b - c) + c(b - c) = (a + c)(b - c)
================================
Автор ответа:
1
Ответ:
(b-c) (a+c)
Объяснение:
a(b-c)-c(c-b)
a(b-c)-c(-(b-c))
a(b-c)+c(b-c)
(b-c) (a+c)
Похожие вопросы
Предмет: Математика,
автор: Ксения105
Предмет: Математика,
автор: fywegjdf1987
Предмет: Литература,
автор: 79371743160
Предмет: Литература,
автор: mikalon
Предмет: Химия,
автор: katrinsomova2